The revival of the Philippine economy - PURISIMA, Cesar V. (Institutional Knowledge at Singapore Management University, 2017)
The former Secretary of Finance for the Philippines and Chair of the Economic Development Cluster from 2010 to 2016, Cesar V. Purisima, talks about the turning around of the Philippine economy and restoring investor confidence, in this interview with Philip Zerrillo.